Techniques for the standard histological and ultrastructural assessment of nerve biopsies. (12th November 2021) - Weis, Joachim; Katona, Istvan; Nikolin, Stefan; Nobbio, Lucilla; Prada, Valeria; Grandis, Marina; Schenone, Angelo
Abstract: It is always a challenge to acquire a clear picture of the pathological processes and changes in any disease. For this purpose, it is advantageous to directly examine the affected organ. Nerve biopsy has been a method of choice for decades to classify peripheral neuropathies and to find clues to uncover their etiology. The histologic examination of the peripheral nerve provides information on axonal or myelin pathology as well as on the surrounding connective tissue and vascularization of the nerve. Minimal requirements of the workup include paraffin histology as well as resin semithin section histology. Cryostat sections, teased fiber preparations and electron microscopy are potentially useful in a subset of cases. Here we describe our standard procedures for the workup of the tissue sample and provide examples of diagnostically relevant findings.